2022
DOI: 10.3389/fimmu.2022.1033774
|View full text |Cite
|
Sign up to set email alerts
|

The carotid body: A novel key player in neuroimmune interactions

Abstract: United States; The idea that the nervous system communicates with the immune system to regulate physiological and pathological processes is not new. However, there is still much to learn about how these interactions occur under different conditions. The carotid body (CB) is a sensory organ located in the neck, classically known as the primary sensor of the oxygen (O2) levels in the organism of mammals. When the partial pressure of O2 in the arterial blood falls, the CB alerts the brain which coordinates cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…This pathway is known to be regulated by a wide range of cytokines like Tnfα as well as growth factors. Importantly, recent studies have shown that CB is a key player in neuro-immune interactions [ 32 , 33 ], and the presence of functional Tnf-α and interleukins (Il-1β, Il-6) receptors that activate CB have been reported [ 34 , 35 ]. Whether the upregulation of the cytokine signaling pathway represents a more generalized pattern of age-dependent development of functional immune competence or contributes to heightened CB hypoxic sensitivity in adults needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is known to be regulated by a wide range of cytokines like Tnfα as well as growth factors. Importantly, recent studies have shown that CB is a key player in neuro-immune interactions [ 32 , 33 ], and the presence of functional Tnf-α and interleukins (Il-1β, Il-6) receptors that activate CB have been reported [ 34 , 35 ]. Whether the upregulation of the cytokine signaling pathway represents a more generalized pattern of age-dependent development of functional immune competence or contributes to heightened CB hypoxic sensitivity in adults needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The CB expresses multiple cytokines (e.g. TNF‐α, IL‐1β, IL‐6) and their receptors and can be activated by increases in these and other blood‐borne inflammatory mediators, causing a compensatory anti‐inflammatory response mediated through sympathetic efferents (Katayama et al., 2022). In the current issue of the Journal of Physiology , a review by Rodrigo Iturriaga, a pioneer in the chemoreception field, discusses the evidence that inflammatory mechanisms reinforce CIH‐induced hypersensitivity of the chemoreflex.…”
mentioning
confidence: 99%